Topology Configuration and Prestress Optimization of Cable-supported Shell with Robustness Evaluation Index. Issue 3 (September 2014) - Shan, Yan-Ling; Wu, Hui; Gao, Bo-Qing
This article finds out the topology configuration and prestress which have the optimal robustness of cable-supported shells as follows. The structure robustness evaluation index is assessed by the H2 norm of system transfer function. The robustness based structure design is transformed into continuum topology optimization by using SIMP material model. The improved Big bang-Big crunch (BB-BC) method employing pseudo-gradient factor is used to get the optimal solution of the topology configuration and prestress joint optimization. Examples show that the improved BB-BC method can solve the joint optimization problems effectively. Topology configuration of the cable-supported shell with a single strut varies with the initial prestress conditions reasonably. The comparison of the joint optimized topology configurations of cable-supported shells with different struts shows that the distribution of material of the shell with five struts is more uniform than that of the shell with a single strut.